Deposition of indium nitride films by activated reactive evaporation process - a feasibility study - Patil, Sheetal J.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Indium nitride (InN) films are deposited by `activated reactive evaporation (ARE)' process using parallel plate coupled nitrogen plasma (radio frequency source of 13.56 MHz) and evaporation of pure indium powder by resistive heating. Depositions are carried out by varying RF plasma power, on n-type silicon &LANGBRAC; 1 0 0&RANGBRAC; substrate, maintained at room temperature, at a nitrogen gas pressure of 1.06 x 10(-1) Pa (8 x 10 (-4) Torr). The film's crystallinity was examined by X-ray diffraction (XRD) and topography by scanning electron microscope (SEM). The diffraction pattern shows polycrystalline nature of the deposited films with characteristics of hexagonal structure. XRD peak intensity increases with increase in power. SEM observations show a smooth and pinhole free surface having improved quality of film with hexagonal structure as the power is increased from 60 to 120 W. Primary X-ray photoelectron spectroscopy (XPS) results show binding energies of the In 3d levels and N 1s level matching well with that of stoichiometric InN. Further, the refractive index of the films, measured by ellipsometry, is in the range of η = 2.79-2.91 with the variation of plasma power, which is in good agreement with the standard value for indium nitride (η = 2.9). These results indicate the feasibility of using, `activated reactive evaporation (ARE)' process for indium nitride depositions on silicon &LANGBRAC; 1 0 0&RANGBRAC; substrates maintained at room temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: activated reactive evaporation; ellipsometry; indium nitride; SEM; XRD

Deposition of PTFE thin films by RF plasma sputtering on < 100 > silicon substrates - Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Polymers have been studied extensively due to the wonderful array of properties presented by them. Polymer materials can be coated/deposited by various techniques like sputtering (magnetron, ion beam, RF or dc), plasma polymerization, etc. and can be used in coatings, paint industries, etc. The present study deals with the RF sputter deposition of poly(tetrafluoro ethylene) (PTFE), commonly known as Teflon. Depositions were carried out on mirror polished silicon (1 0 0) substrates at different powers in the range of 100-200 W. The deposition time was kept constant at 60 min. The sputtered film shows lower contact angle of 50&DEG; with water and 44&DEG; with diiodomethane, a lower interfacial tension value of 0.76 dyne/cm, indicating hydrophilicity and good adhesion of the film with the substrate. FHR indicates presence of C-F, C-F-2 bonding groups in the deposited film. Further, XPS study shows presence of CF3 (292.2 eV), CF2 (290.8 eV), C-F (288.0 eV) and C-CF (286.4 eV) moieties indicating deposition of PTFE films at higher power levels of plasma. © 2004 Elsevier B.V. All rights reserved.
Keywords: Contact angle measurement; FTIR; PTFE; RF plasma sputtering; XPS

Electron beam induced surface cross-linking of functional monomers coated on silicon substrate - Mahapatra, S. K.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A.; Bhoraskar, Vasant N. (Materials Letters, 2006)
A 3: 1 composition of functional monomer: multifunctional acrylate was spin coated and later cross-linked under the influence of keV electron irradiation on the surface of silicon to generate a surface-anchored cross-linked network bearing functional moieties. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) as well as wetting angle measurements were used for the analysis of functional monomer cross-linked surfaces. Results of the surface reconstruction of surfaces and electron irradiated on coated silicon wafers reveal that long-term hydrophilic surfaces can be achieved. Thus, the surface architecture can be favorably manipulated by using this remarkable technique with a Suitable combination of functional monomers and cross-linkers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electron beam irradiation; FTIR; Polymers; surface modification; XPS

Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.